PERISTILAHAN TUMBUHAN DALAM PERIBAHASA MASYARAKAT MELAYU SAMBAS - Afriyanti Afriyanti; Patriantoro Patriantoro; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThe terminology of plants in the Sambas malay society proverb in this study is seen from the form, the lexical meaning, the meaning of the analogy, and the cultural meaning. The method used in this research is descriptive linguistics. The approach used in this research is the ethnolinguistic approach. The data source of this research are primary data and secondary data. Primary data of this study were taken from the field orally from informants. Secondary data in this research is the data written as corpus data obtained from the book "1001 PantunPeribahasa" by Sudiadi. Techniques used in this study, namely interviewing techniques, record and note, and documentation. Data collection tools in the research, namely voice recorder and notebook. Based on research conducted, the researchers succeeded in collecting 65 terms of plants in the adage of Sambas malaysociety. The overall data is obtained from the interview and recording process. Plant terminology in the study consists of three terms, namely monomorphemic (single word) of 32 terms, polymorphism (derived words) of 5 terms, and phrases as many as 28 terms. The term of the plant as a whole has the meaning of as many as 65 lectical terms. the meaning of the analogy of 65 terms, and the cultural sense of 26 terms. Keywords: Terminology, Plant, Proverb Of Sambas Malay Society.